Multimodal radar with wide band communication system - Danial Ritzuan Junaidi (Nanyang Technological University, 2020)
A multimodal radar is a radar that is capable of carrying out multiple radar applications. Such applications could vary from map imaging, moving target detection to doppler radar and they may also differ in their electromagnetic wave propagation from Line-of-Sight (LOS) to Non-LOS [1]. With that in mind, this project involves working with two distinct radar systems, namely a Drone-Based (LOS), Synthetic Aperture Radar (SAR) Imaging System and a Wall Penetration (Non-LOS), Frequency Modulated Continuous Wave (FMCW) Moving Target Detection Radar System. Synthetic Aperture Radar (SAR) Imaging is one of the most important surveillance techniques nowadays due to its all-time and all-weather operation capability [2]. SAR is a coherent, airborne or spaceborne side-looking radar system which makes use of the flight path of the platform it is mounted on to simulate an extremely large antenna or aperture electronically, thereby generating a high-resolution remote sensing imagery [3]. On the other hand, a Wall Penetration Radar makes use of electromagnetic wave propagation to detect through visually opaque materials of buildings and man-made structures for humans and moving objects [4]. In principle, Wall Penetration Radars must use low frequencies that range from Ultra High Frequency (UHF) to S-band so as to maximise the wall electromagnetic transmission [5]. Depending on how long the radar is set to scan and record the area for targets, the size of the raw data collected could be rather large. To put it simply, the longer the radar records, the larger the data size. Hence, to ensure a real time, fast downlink transmission of the data from the radar platform to the ground/base station, a wideband communication system will be used to carry large amounts of information [6]. As such, next generation 5G or Wi-Fi 6 could be explored to determine their potential suitability for this application since they are the latest technology to date.